Species discovery and diversity in Lobocriconema (Criconematidae: Nematoda) and related plant-parasitic nematodes from North American ecoregions - Powers, T.o.; Bernard, E.c.; Harris, T.; Higgins, R.; Olson, M.; Olson, S.; Lodema, M.; Matczyszyn, J.; Mullin, P.; Sutton, L.; Powers, K.s. (Zootaxa, 2016)
There are many nematode species that, following formal description, are seldom mentioned again in the scientific literature. Lobocriconema thornei and L. incrassatum are two such species, described from North American forests, respectively 37 and 49 years ago. In the course of a 3-year nematode biodiversity survey of North American ecoregions, specimens resembling Lobocriconema species appeared in soil samples from both grassland and forested sites. Using a combination of molecular and morphological analyses, together with a set of species delimitation approaches, we have expanded the known range of these species, added to the species descriptions, and discovered a related group of species that form a monophyletic group with the two described species. In this study, 148 specimens potentially belonging to the genus Lobocriconema were isolated from soil, individually measured, digitally imaged, and DNA barcoded using a 721 bp region of cytochrome oxidase subunit 1 (COI). One-third of the specimens were also analyzed using amplified DNA from the 3’ region of the small subunit ribosomal RNA gene (18SrDNA) and the adjacent first internal transcribed spacer (ITS1). Eighteen mitochondrial haplotype groups, falling into four major clades, were identified by well-supported nodes in Bayesian and maximum likelihood trees and recognized as distinct lineages by species delimitation metrics. Discriminant function analysis of a set of morphological characters indicated that the major clades in the dataset possessed a strong morphological signal that decreased in comparisons of haplotype groups within clades. Evidence of biogeographic and phylogeographic patterns was apparent in the dataset. COI haplotype diversity was high in the southern Appalachian Mountains and Gulf Coast states and lessened in northern temperate forests. Lobocriconema distribution suggests the existence of phylogeographic patterns associated with recolonization of formerly glaciated regions by eastern deciduous forest, but definitive glacial refugia for this group of plant parasitic nematodes have yet to be identified. Unlike agricultural pest species of plant-parasitic nematodes, there is little evidence of long-distance dispersal in Lobocriconema as revealed by haplotype distribution. Most haplotype groups were characterized by low levels of intragroup genetic variation and large genetic distances between haplotype groups. The localization of nematode haplotypes together with their characteristic plant communities could provide insight into the historical formation of these belowground biotic communities.